Social Media Addiction and Depression Among University Students - Qamrosh Akhlaq; Ms. Maria Bashir; Dr. Lubna Zafar; Syed Jawad Zareen (Research Journal of Psychology, 2024)
This study aimed to investigate the effects of social media addiction on depression in adult individuals. For this purpose, the researcher analyzed whether social media dependence had differing impacts according to various variables (age, gender, the highest level of education, duration of daily use of social media, frequency of social media use, etc.). A sample population of Students of University of Poonch Rawalakot in different campuses such as supply campus , shell campus , agriculture campus between 18 to 30 years of age participated in the research .The questionnaire form was developed to obtain the Social Media Addiction Scale (SMAS), Beck Depression Inventory scores, and demographic information from the participants. . Significant differences were found between depression and social media dependency in variables such as the number of children, age, and income. As a result of the study, when social media addiction was examined in terms of gender among socio-demographic variables, no significant difference was found. Key words: Social Media, Depression, University Students